Comparative analysis of production cost and regeneration efficiency in tissue culture across different banana cultivars / Nur Hazirah Ismail - Ismai, Nur Hazirah (Faculty of Plantation and Agrotechnology, 2018)
Micropropagation or tissue culture is a highly efficient technique of in vitro propagation that allowing the production of large number of planting materials in a short period of time. A comparative study on the regeneration efficiency and production cost of three different banana cultivars namely Musa acuminata cv. Berangan, Tanduk and Nangka was carried out. The aims of the current study were to compare the regeneration efficiency across three selected banana cultivars and identify the cultivar which is most cost-efficient to be propagated through tissues culture technique. The banana suckers were collected and used as the explant and cultured on Murashige and Skoog (MS) medium supplemented with 5 mg/L of BAP and 1 mg/L of NAA. Among the three banana cultivars studied, Berangan showed the highest regeneration efficiency and the lowest production cost. Through this study, uniform size and disease-free planting materials were produced. Besides, the production costs of the selected banana cultivars were determined.